Chemical Modification of tropical wood polymer composites for value-added applications - Md. Saiful, Islam (Universiti Malaysia Sarawak, (UNIMAS), 2012)
In this study, several types of tropical light hardwoods were chemically modified by the traditional and combined with nanotechnological process through impregnation method. All these wood were treated with various types of chemicals formulations such as (i) combination of Methacrylate (MMA) and Hexamethylene diisocyanate (HMDIC) (ii) Methacrylate/Styrene (iii) Benzene diazonium salt and (iv) Phenol formaldehyde-Nanoclay (PF-Nanoclay) prepolymer to modify and convert them into wood polymer composites (WPCs) and wood polymer nanocomposites (WPNcj)The chemical reaction with wood, morphological change and formation of wood composite were confirmed through fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis. The mechanical properties in terms of modulus of elasticity (MOE), modulus of rupture (MOR), compressive modulus and dynamic Young's modulus (Ed) were found to be improved on treatment. However, PF-Nanoclay impregnated WPNC samples exhibited better improvement on properties over raw wood, WPC and treated one. Thermal properties of wood were evaluated using thermogravimetric anaiysis (TGA) and differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMT A). HMDIC as a crosslinker significantly improved the physico-mechanical, thermal and decay resistance properties of WPC. The reaction between wood and HMDIC and crosslinked with MMA was confirmed from the FTIR spectrum in which absorption band of 1736 cm-1(C=O) disappeared and the new absorption band at 3359 cm-1 due to the carbamate N-H bonds appeared. The SEM image and XRD pattern reveal a polymer filled smoother surface texture and improved degree of crystallinity. Significant improvement in wood mechanical and morphological properties such as MOE, MOR, compressive modulus, SEM micrographs and XRD pattern were observed for the alkali pretreated WPC samples. The reactions of NaOH with cellulose in wood fibre yielded cellulose-~Na compound which was confirmed by FTIR spectrum. This study also examined the influence of coupling reaction on the physical, mechanical, thermal properties of modified wood. Benzine diazonium salt reacted with cellulose in wood and produced 2, 6-diazo cellulose by a coupling reaction, as confirmed by FTIR spectrum. The physico-mechanical, thermal and decay resistance properties were found to be improved on treatment. However, the MOR of wood samples was shown to be decreased on treatment. III Moreover, the treated wood samples had higher surface hardness compared to the untreated one. The effect of nanoclay on the morphological, mechanical and thermo-mechanical properties of WPNC was investigated. The incorporation of nanoclay inside wood and formation of WPNC was confirmed through FTIR, energy-dispersive X-ray spectroscopy (EDX) and SEM respectively. The mechanical and thermo-mechanical properties of WPNC improved significantly by the PF-Nanoclay treatment. The storage modulus (E) of the WPNC samples exhibited significant improvement in both glassy region and rubbery plateau in relation to their corresponding raw wood and WPC. Furthermore, the damping (loss tan8) peaks of woods seemed to be lowered by the treatment with PF-Nanoclay system. A significant improvement on decay resistance was also found in the WPNC samples compared to WPC and raw ones. The improvement m properties was observed as more potential with the PF-Nanoclay treatment among the above all modifications techniques.